Sustainable Analysis of Lightweight Lift System Design for Disable People Using Finite Element - Mohd Yusof, Taib; S. F., Ismail; M., Ishak (2011)
Lift is a kind of system in building to move people vertically. In Malaysia, most of lifts in the buildings are available only five levels and above. Thus, the movements of disable people below than five levels are limited. There are the idea of the design and analysis of light weight and lift system for the use of disable people is developed. The aim of design is transporting a disable people using wheelchair from ground floor to first floor. Design concept of lift is based on rails, electric motor and gears. The structural and component model of lift it developed using the CAD software. The three dimension solid model is then imported to the FEM software to analyze the suitainable of the lift system. Thus, stress and strain relation was figured to identify the behavior of elastic limit and the strength of structure to resist the application of forces acting without breaking.